Investigating Possibilities to Provide Collaborative Learning Spaces in Libraries for Children with Special Needs - Jaya Laxshmi, Meenatchisundaram; Dayang Norsheila, Abang Mohtar; Fitri Suraya, Mohamad (Universiti Malaysia Sarawak, UNIMAS, 2014)
While opportunities for technology-based collaborative learning have reached out to a large majority of the community, not everyone has been able to benefit from the growth of collaborative learning. Computer supported collaborative learning (CSCL), in particular, has great potential for children with special needs in terms of building social interaction and collaborative skills through the use of various information and communication technology (ICT) tools. This paper presents a preliminary investigation on how library spaces could be utilised to encourage collaborative learning skills for children with special needs. Gaps in literature with regards to the usage of library spaces for this purpose as well as the limitations of current tools in terms of language diversity are also explored. Future research directions are also presented to position plausible strategies to use libraries as spaces for collaborative learning for children with special needs, using appropriate tools to support their learning process and experience.